Does state ownership affect R&D investments? Evidence from China - Ala'a Azzam; Salem Alhababsah (Cogent Business & Management, 2022)
This study provides up-to-date evidence concerning the relationship between government ownership and R&D investments in the Chinese context. Using a large sample comprised of 15,138 observations from A-share firms traded on the Shanghai and Shenzhen stock exchange between 2009 and 2018, the findings show that government ownership has a positive impact on R&D investment decisions. Furthermore, a supplementary test confirms that government ownership has also a positive impact on board monitoring intensity, as measured by the frequency of board meetings. This study injects the literature with fresh evidence on the role of state ownership in R&D investment in China, especially after the most recent wave of privatization, namely Split-Share Structure Reform (SSSR) which started in 2005. The results of this study have implications for different stakeholders as they do not support the common impression regarding the negative impact of state ownership on business outcomes.
Keywords: G34; G38; O32; 650; China; R&D; State ownership